Central regulation of appetite in birds: Recent advances and future perspective - Mahdavi, Kimia; Zendehdel, Morteza; Zarei, Hamed (Journal of Poultry Sciences and Avian Diseases, 2023)
Understanding the mechanism of food intake is important for comprehending energy balance, obesity, and the body weight regulation. In particular, examining birds’ appetite is critical for conservation efforts, managing human-bird interactions, and understanding the environmental implications of bird feeding practices. In this systematic review, using the PRISMA guideline, we investigated the mediators that were identified as factors affecting the birds’ appetite in 2022 and 2023. In order to obtain the appropriate studies, suitable keywords were searched in the relevant electronic databases and an anthology of the desired articles was done. According to the findings, the central administration of adrenomedullin, apelin-13, lipopolysaccharide, neuromedins and spexin causes hypophagia in chickens, while the injection of adiponectin, neuropeptide W (NPW) and phonexin-14 increased the food intake of birds. Also, regarding the members of RF-amide peptide family, neuropeptide VF (NPVF) and neuropeptide FF (NPFF) weakened the food consumption of birds, while kisspeptin and prolactin-releasing peptide (PrRP) strengthened it. The effects observed in birds were similar to mammals in most cases, indicating the structural and general similarities in the regulatory mechanisms of these strains, on the other hand, the contradictory effects between the two species were probably caused by genetic differences. Finally, despite the progress made in identifying the factors and mechanisms involved in regulating the appetite of birds, it is recommended to conduct future studies using modern laboratory methods, especially cellular-molecular methods.